The Impact of Hypernatremia in Preterm Infants on Neurodevelopmental Outcome at 18 Months of Corrected Age - Howell, Heather B.; Lin, Matthew; Zaccario, Michele; Kazmi, Sadaf; Sklamberg, Felice; Santaniello, Nicholas; Wachtel, Elena (American Journal of Perinatology, 2020)
Objective The study objective was to assess the correlation between hypernatremia during the first week of life and neurodevelopmental outcomes at 18 months of corrected age in premature infants.Study Design A retrospective observational study of preterm infants born at less than 32 weeks of gestation who had a neurodevelopmental assessment with the Bayley scales of infant and toddler development III at 18 ± 6 months of corrected age. Serum sodium levels from birth through 7 days of life were collected. The study cohort was divided into two groups: infants with a peak serum sodium of >145 mmol/L (hypernatremia group) and infants with a peak serum sodium level of <145 mmol/L (no hypernatremia group). Prenatal, intrapartum, and postnatal hospital course and neurodevelopmental data at 18 ± 6 months were collected. Logistic regression analysis was used to assess the correlation between neonatal hypernatremia and neurodevelopment with adjustment for selected population characteristics.Results Eighty-eight preterm infants with complete neurodevelopmental outcome data at 18 ± 6 months of corrected gestational age were included in the study. Thirty-five neonates were in the hypernatremia group and 53 were in the no hypernatremia group. Maternal and neonatal characteristics were similar between the two groups except that the hypernatremia group had a significantly lower average birth weight and gestational age. Comparison of the mean neurodevelopmental scores between the two groups showed that patients in the hypernatremia group as compared with those in the no hypernatremia group had significantly lower neurodevelopmental scaled scores in the fine motor domain (p = 0.01). This difference remained significant (p = 0.03, odds ratio [OR] = 0.8, 95% confidence interval [CI]: 0.6–0.97) when adjusted for birth weight and gestational age.Conclusion Preterm infants born at less than 32 weeks of gestation with hypernatremia in the first week of life have lower fine motor scores at 18 months of corrected age.Key Points
Keywords: prematurity; neurodevelopment; hypernatremia; preterm infant; dysnatremia